Improved Learning Achievement About How to Introduce Oneself Through the Scientific Approach of Video Media - Istina Dewi Puji Astuti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve the learning achievement of students in Indonesian Language Mupel in Elementary Class 1 through a scientific approach with video media. The research conducted was a Classroom Action Research (CAR )in three cycles, which each cycle consisting of one meeting.The stage of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out a pre test and post test to determine the progress of students. In the first cycle students who completed after carrying out the post test were 50%. In the second cycle students who completed after carrying out the post test were 85, 71%. In the third cycle students who completed after carrying out the post test were 92,85%. These results indicate that learning through a scientifik approach with video media can improve student learning achievement, especially Mupel Indonesian Language on How to Introduce Yourself in Class 1 SDN Plosogede 1.